Tai Chi pushing hands and sublimation of life - Li, Chenxiao (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: After Wei Lei (" Lei Gong Tai Chi ") and Ma Baoguo (" Huanyuanyingyi Tai Chi ") failed to compete in public, modern media society strongly questioned the actual combat of traditional martial arts such as Tai Chi and even traditional martial arts itself. Most of the Chinese people’s cognition of Taijiquan is inclined to be one-sided, superficial and extreme. As a training method for Tai Chi people to perceive and apply power, Tai Chi pushing hands is an important part of Tai Chi practicing. Combined with the practice mode of Tai Chi pushing hands, this paper analyzes the great value of the practice to the sublimation of the practitioner’s life, so as to provide the reader with a relatively objective perspective and refresh the cognition of Tai Chi. Methods: Literature method, field observation method, logical analysis method and so on. Results: 1) Tai Chi pushing hands can greatly improve human body function in a gentle training way. After more than three hundred years of inheritance and development, Tai Chi pushing hands training has formed a system and continues to improve. Tai Chi pushing hands is highly restricted in rules and prohibits the use of kicking, hitting, throwing, holding, grasping and other harmful means. It is a mild game sport. Our predecessors practiced in a closed way, and it was only in modern times that they gradually opened it up. In addition, it is difficult for the majority of people to understand the mystery directly from the visual perspective, so it is easy to misunderstand, and they treat and compare pushing hands with other fighting sports, which is far from the original meaning of this item. It is a harmonious, friendly and win-win sport, which is full of interest and entertainment. It is a unique, professional and staged training, which cannot be compared with other confrontational sports. Through learning and gradually mastering the use of Tai Chi vitality skills, can accelerate the opening of the human microcirculation. Sensitivity, speed, coordination and other original functions will be greatly improved. The most prominent is to greatly reduce the occurrence of injuries in the process of various antagonism training, which is unique in any combat sport and one of the highlights of this item. 2) Tai Chi pushing hands can develop people’s inner wisdom imperceptibly with the thoughts of subtle profound. Tai Chi pushing hands is the application and expression of Taoist thought in Tai Chi. Push-hand training enables people to understand what Yin and Yang are, and how to use the principle of mutual use and transformation of Yin and Yang, and gradually sublimate to the understanding of emptiness. This sport enables people to establish the concept of keeping soft and not fighting, to achieve the realm of to do nothing is to do nothing. In combination with their own circumstances after trying to flexibly use, can players using little strength overcomes a great power, conquering the unyielding with the yielding, using weak force overcame a powerful opponent. After practicing Tai Chi pushing hands and translating the ideas and technical movements into daily life, the essence of the thought inherited through the ages can be transferred to life. When confronted with difficulties, it is more open-minded and cheerful, more generous and lenient in dealing with people, and be more calm and detached in daily life. In the general circulation of the Tai Chi circle, insight into extreme Yin is followed by extreme Yang, after extreme Yang comes extreme Yin, understanding there misfortune connect with bliss and after a storm comes a calm, clearly understand the laws of the universe which is that all the things is empty and not available. Not to walk the world cramped by mode, not disorderly by a lot of things, not to lost one’s conscience. Accomplish a task with ease in the lyre, chess, calligraphy, painting, poem, wine, flowers, firewood, rice, oil, salt, sauce, vinegar and tea. Free and unfettered with the shining spears, armoured horses and blooming flowers in all their beauty. From the melt of empty and exist return to the middle way. 3) Tai Chi pushing hands can enhance the vitality of people’s life with a broad cultural like the spring rain moistens the nursery. Tai Chi pushing hands including dynamic and static, which can help players reach to void and static extremely in dynamic interaction. So it is a good recipe for people to slow down in the fast-changing world and find a sense of belonging to the nature. Tai Chi pushing hands is designed to emphasize simplicity while it seems to promote weakness. It teaches us how to handle complexity with simplicity and maintain inner peace in a complex world. Tai Chi pushing hands emphasizes keeping the tathagata, "Going too far is as bad as not going far enough", "impartial" explains balance and harmony, which can gradually make people give up unnecessary material fetter and fill their own spiritual world when materialized thought is popular in a large area of the world. Tai Chi pushing hands let players summon up courage to experience a total flow of emotions in every moment of their lifeuse, see their diverse world inside, feel their own heart change rapidly, realize self liberation and transcendence, make their own life into the enduring vitality and keep it in a state of fresh, let the flower of life bloom more colorful. Conclusion: as a key link of Tai Chi practice, Tai Chi pushing hands is a means of strengthening the body and prolonging life, a channel for enlightening wisdom and understanding nature, a light to explore life and enhance vitality. On December 17, 2020, Tai Chi was successfully inscribed on the UNESCO’s Representative List of the Intangible Cultural Heritage of Humanity, further enhancing its international influence. It is believed that the beautiful rhyme of Tai Chi pushing hands will change the bad impression of fake and inferior martial arts, clown gymnastics and "bastard" skills in the minds of some Chinese people, and the "Lei Gong Tai Chi" and "Ma Baoguo event" will also provide a revolutionary and positive element for the reconstruction of the traditional Chinese martial arts world. After Chinese martial arts has gone through the tortuous road, it will surely usher in a vast and lofty tomorrow.